A Study on Job Satisfaction of Woman Workers in Fireworks Industries in Tamil Nadu - Ketharaj, M.; Selvakumar, M. (Indian Journal of Marketing, 2009)
The development of any nation primarily depends upon its industrial development which makes rich contribution to the growth of a nation. The economic role played by women cannot be isolated from the framework of development. Women workers remain significantly poor and are far less legally protected.The role of women in socio-economic development has undergone a marked change over the years. The world of women is no longer confined to household activities. Today, they actively contribute to the promotion of economic development in different capacities.